A Biomechanical Comparison of Two Intramedullary Implants for Subtrochanteric Fracture in Two Healing Stages: A Finite Element Analysis. (23rd February 2015) - Wu, Xinlei; Yang, Ming; Wu, Lijun; Niu, Wenxin
Abstract : Background . The biomechanical effect of two implants, namely, proximal femoral nail antirotation for Asia (PFNA-II) and Expert Asian Femoral Nail (A2FN), for treating subtrochanteric fracture during healing stages, is still unclear. Methods . A 3D finite element model of an intact femur was constructed and validated. The fractured and postoperative models were accordingly produced. The postoperative models were loaded with the peak joint forces during gait for the soft and hard callus stages. The effects of stress distribution on the implants, femoral head and callus, and the deformation of the proximal femur were examined. Results . Both implants showed similar biomechanical effect in two healing stages. As the healing duration increased, the von Mises stress of two implants and the tensile stress of the femoral head decreased, whereas the compressive stress of the femoral head increased. However, the PFNA-II operation resulted in higher stress on the implant, lower stress on the proximal femur, and lower compressive stress and higher tensile stress on the callus than A2FN operation. Conclusions . The A2FN implant may provide a biomechanically superior construct for subtrochanteric fracture healing. However, the upper screw of the A2FN implant may be more likely to be loose in the healing process.